Reassessing the Supreme Court: How decisions and negativity bias affect legitimacy - Christenson, Dino P.; Glick, David M. (Political Research Quarterly)
While the Supreme Court$1 (Bs legitimacy is generally considered essential to its influence, scholars continue to debate whether the Court$1 (Bs decisions affect individuals$1 (Bassessments of it. The last week of the 2013 term provides an unusual opportunity to evaluate these issues because the Court made a conservative decision concerning the Voting Rights Act (VRA) only one day before it made a liberal one about same-sex marriage. We use original panel data of individuals$1 (Bviews throughout this period, including a wave collected on the day between the two decisions, to investigate the links among decisions and legitimacy. We find that diffuse support for the Court is sensitive to decisions in these two salient cases conditional on individuals$1 (Bideological distance to the Court and their policy support. Moreover, the negative effects of an unfavorable decision are stronger than the positive effects of a favorable one. - Reproduced.s